History of Organizational Sociology and Classical Sociological Theory - Akdila Bulanov; Fanisa Mutiara; Wafiq Azizah; Siti Aisyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article examines the historical development of organizational sociology and the contribution of classical sociological theory to understanding modern organizational dynamics. Organizational sociology emerged alongside social transformations driven by industrialization and modernization, which encouraged the formation of structured institutions to manage collective human activities. This study employs a qualitative approach using library research methods by analyzing relevant sociological literature, classical theoretical works, and contemporary academic sources. The analysis focuses on the ideas of classical sociologists, namely Auguste Comte, Karl Marx, Émile Durkheim, and Max Weber, whose theoretical perspectives laid the foundation for organizational analysis. The findings show that organizational sociology developed as an extension of classical sociological thought, emphasizing scientific approaches, social solidarity, power relations, division of labor, and bureaucratic rationality. Classical sociological theories remain relevant in explaining contemporary organizational phenomena, including leadership, institutional structure, work relations, and organizational effectiveness in the modern era. Understanding the historical roots of organizational sociology provides a comprehensive framework for analyzing organizational changes in response to globalization and technological development in the 21st century.